Companion to the Political Economy of Rent Seeking 2015
DOI: 10.4337/9781782544944.00012
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in rent seeking

Abstract: In rent-seeking contests, players are seldom identical to one another. In this chapter, we examine the rent-seeking literature that explores the effects of specific forms of asymmetry between contestants. We consider Tullock's rentseeking contests involving two players who differ in strength (marginal returns to effort), motivation (valuations of the sought-after rent) and cunning (bargaining power). We study the combined interaction of these three possible forms of asymmetry in rent-seeking. We examine how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…26 These results are interesting when compared to other asymmetries in litigation contests. Dari-Mattiacci et al (2015) showed that asymmetries in parties' payoffs and efforts may arise in the presence of asymmetries in marginal returns to effort, valuations of the rent, and bargaining power. The contour-plot 2b shows the values of the individual equilibrium effort under different combinations of the evidence standards and the objective merits of the case.…”
Section: Litigation Efforts and Equilibrium Behaviormentioning
confidence: 99%
“…26 These results are interesting when compared to other asymmetries in litigation contests. Dari-Mattiacci et al (2015) showed that asymmetries in parties' payoffs and efforts may arise in the presence of asymmetries in marginal returns to effort, valuations of the rent, and bargaining power. The contour-plot 2b shows the values of the individual equilibrium effort under different combinations of the evidence standards and the objective merits of the case.…”
Section: Litigation Efforts and Equilibrium Behaviormentioning
confidence: 99%
“…The party with the largest cost of effort can effectively choose among a more restricted set 1 For recent reviews, see Konrad (2008a, 2008b); Congleton and Hillman (2015). A review of the literature on asymmetric rent-seeking games, which will form the basis for our model, can be found in Dari-Mattiacci and Parisi (2015).…”
Section: Introductionmentioning
confidence: 99%
“…The exception occurs in the very particular case in which the returns to scale in the production of legal arguments are decreasing and sufficiently low (Farmer and Pecorino, 1999). 3 However, in this case, the introduction of realistic considerations, such as, for example, asymmetries between individuals, outside options or other aspects is analytically intractable (Dari-Mattiacci et al, 2015). Analytical tractability can be recovered by assuming constant returns to scale in the production of legal arguments, but then, as explained, no case reaches trial under the English system, which is counterfactual; 4 thereby restricting to a great extent the generalized application of the "rent-seeking" CSF, and questioning whether this approach to litigation is complete enough.…”
Section: Introductionmentioning
confidence: 99%